RESPON TIGA VARIETAS CABAI MERAH (Capsicum annum L.) TERHADAP DOSIS BOKASHI CAMPURAN REMUNGGAI (Moringa oleifera) DAN DAUN JAMBU AIR (Syzygium aqueum) - Chusniyah, Shofiyatul; Nurseha; Rustianti, Sri (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
This experiment aims to determine the response of several red chili varieties to doses of bokashi mixed with remunggai (Moringa oleifera)and water apple leaves (Syzygium aqueum). This research was conducted from December 2022 to April 2023 in Bukit Peninjauan 1 Village, Sukaraja District, Seluma Regency. Using a completely randomized factorial design. The first factor was variety (V) which consisted of V1: Panex 100, V2: Pilar, V3: Gada MK, and the second factor was the dose of bokahi (D) which consisted of D1: control (NPK), D2: 10 tonnes/ha, D3: 20 tonnes/ha, B4: 30 tonnes/ha. The treatment was repeated 3 times to produce 36 experimental units. The results of the analysis of variance were continued with the Duncan's Multiple Range Test (DMRT) with a level of 5% if the factors had a significant or very significant effect. The results of the research that has been done show that giving different doses of bokashi to 3 varieties of chili plants has no significant effect on all observed variable parameters, both plant height, number of branches, flowering age, harvesting age, number of fruits per plant, and fruit weight planted.